Low rate of subsequent surgery and serious complications following intra-articular steroid injection for base of thumb osteoarthritis: national cohort analysis - Lane, JCE; Craig, RS; Rees, JL; Gardiner, MD; Shaw, AV; Spiteri, M; Kuo, R; Dean, BJF; Green, J; Prieto-Alhambra, D; Furniss, D (Oxford University Press, 2021)
Objectives: Intra-articular steroid injection is commonly used to treat base of thumb osteoarthritis (BTOA), despite a lack of large-scale data on safety and effectiveness. We estimate the incidence of serious complications and further procedures following BTOA injection, including the risk of post-operative serious surgical site infection for subsequent operative intervention.